POLA ASUH ORANG TUA DALAM PEMBENTUKAN KARAKTER MANDIRI ANAK SELAMA PEMBELAJARAN TATAP MUKA TERBATAS - Nur Ajrie; Erik Aditia Ismaya; Muhammad Rizal Fauzi; Khotimatus Saadah (P2M STKIP Siliwangi, 2022)
This study aims to determine the application of parenting and its impact on the independent character of fourth graders at SDN Banyuurip 02. In this study, researchers used phenomenological research using a qualitative approach. This research was conducted on the parents of 3 class students. Data collection techniques include interview, observation, and documentation techniques. The data validity test in qualitative research includes credibility, transferability, dependability, and confirmability tests. While the data analysis techniques in this study are data reduction, data display, and conclusion drawing/verification. The results showed; (1) the application of parenting patterns; (a) democratic parenting, (b) authoritarian parenting; and (c) permissive parenting and (2) the impact of applying parenting styles; (a) democratic parenting, in general democratic parents show expressions of love and responsiveness to their children; (b) authoritarian parenting, creating feelings of anxiety, fear, inferiority and lack of respect and lack of confidence in children, easily offended, timid, moody, and easily influenced; and (c) permissive parenting, this pattern will shape the child's personality which is not good, the negative impact is that the child tends to be less tenacious in trying to achieve something, quickly leaves difficult tasks, demands more immediate gratification without serious effort.